2002
DOI: 10.1111/j.1559-1816.2002.tb01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Rodney King and O. J. Revisited: The Impact of Race and Defendant Empathy Induction on Judicial Decisions

Abstract: White university students participated in a study to investigate the impact of defendant race and empathetic induction on a subsequent juror decision‐making task. Participants read a passage involving a Black or a White defendant in a criminal case. They were subsequently induced to feel no empathy, low empathy, or high empathy for the defendant. When compared to participants in the low‐ and control empathy conditions, those in the high‐empathy condition reported greater target empathy, made attributions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 33 publications
3
70
0
1
Order By: Relevance
“…Unfortunately, this categorization also maximizes diferences between groups, leading people to more readily distrust, fear, and discriminate against outgroup members and to instinctively favor or side with members of social groups with which they identify [32].…”
Section: Intergroup Empathy Biasmentioning
confidence: 99%
“…Unfortunately, this categorization also maximizes diferences between groups, leading people to more readily distrust, fear, and discriminate against outgroup members and to instinctively favor or side with members of social groups with which they identify [32].…”
Section: Intergroup Empathy Biasmentioning
confidence: 99%
“…These characteristics have particular consequences for decisions involving morality and emotional empathy, such as those commonly confronted by jurors. Research has demonstrated that when empathy is induced in non-psychopathic individuals, the feeling of empathy is associated with greater resource allocation (Batson, Klein, Highberger, & Shaw, 1995), situational attributions of defendant responsibility, and more lenient sentencing outcomes (Johnson et al, 2002).…”
Section: Psychopathic Traitsmentioning
confidence: 99%
“…Perception of others in pain or distress generates empathic concerns that provide a proximate mechanism selected by evolution that motivates altruistic behaviors (Batson, 1991;de Waal, 2008). Empathy may influence social behaviors by changing people's attitudes toward a target (Batson et al, 1997a), which sometimes produces serious consequences such as when making judicial decisions on a defendant (Johnson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence supporting this hypothesis comes from research that measured subjective reports of empathic concern. Johnson et al (2002) asked White university students to read a passage involving a Black or a White man who was charged with a criminal act. Participants were induced to feel no empathy, low empathy, or high empathy for the defendant and then evaluate punishments applied to the defendant.…”
Section: Introductionmentioning
confidence: 99%